Controlling android device with eye tracking - Hasan, Sakib; Tamim, Md. Tahsin Alam; Robin, S. M. Tarequl Hasan; Tasnim, Sadia; Mahmud, Shah Tanvir (BRAC University, 2017)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2016.